Mathematical analysis of the equivalent impedance at the harmonic frequency for the proposed aircraft power system - Zhou, Qian; Sumner, Mark; Thomas, Dave (Institution of Engineering and Technology, 2013)
The proposals for the `More Electric Aircraft' place a significant, increased demand on the electrical power distribution system. To increase safety and reduce aircraft maintenance times on the ground, there is a greater need to quickly identify and locate electrical faults within the electrical distribution system. The work presented in this study provides the mathematical basis for the use of power system harmonic impedance measurement for identifying and locating faults within power cables. The method is passive - that is, it does not require the injection of any test signals - and can potentially be embedded into a centralised equipment controller to provide intelligent, real time diagnostics. The method monitors the harmonic line-line self-impedance at strategic points in the distribution system; this is obtained by measuring load voltage and current. Faults can be identified and located within a few fundamental cycles, and therefore provides a `backup protection' system which does not require measurement of the line current. It also can provide details of the fault location and could therefore be a significant aid to aircraft maintenance. This study derives the theoretical basis of the scheme and provides simulation results for a proposed aircraft power system to demonstrate the validity of this approach to detect and locate faults within the system.